Evaluation of four-dimensional cone beam computed tomography ventilation images acquired with two different linear accelerators at various gantry speeds using a deformable lung phantom. (September 2020) - Kadoya, Noriyuki; Nemoto, Hikaru; Kajikawa, Tomohiro; Nakajima, Yujiro; Kanai, Takayuki; Ieko, Yoshiro; Ikeda, Ryutaro; Sato, Kiyokazu; Dobashi, Suguru; Takeda, Ken; Jingu, Keiichi
Highlights: We evaluated VICBCT obtained with TrueBeam and Versa HD at various gantry speeds. Jacobian-based VICBCT had better agreement with the VICT compared with the HU-based VICBCT . The Versa HD VICBCT had higher agreement with the VICT than the TrueBeam VICBCT . Abstract: We evaluated four-dimensional cone beam computed tomography (4D-CBCT) ventilation images (VICBCT ) acquired with two different linear accelerator systems at various gantry speeds using a deformable lung phantom. The 4D-CT and 4D-CBCT scans were performed using a computed tomography (CT) scanner, an X-ray volume imaging system (Elekta XVI) mounted in Versa HD, and an On-Board Imager (OBI) system mounted in TrueBeam. Intensity-based deformable image registration (DIR) was performed between peak-exhale and peak-inhale images. VICBCT - and 4D-CT-based ventilation images (VICT ) were derived by DIR using two metrics: one based on the Jacobian determinant and one on changes in the Hounsfield unit (HU). Three different DIR regularization values (λ) were used for VICBCT . Correlations between the VICBCT and VICT values were evaluated using voxel-wise Spearman's rank correlation coefficient (r). In case of both metrics, the Jacobian-based VICBCT with a gantry speed of 0.6 deg/sec in Versa HD showed the highest correlation for all the gantry speeds (e.g., λ = 0.05 and r = 0.68). Thus, the r value of the Jacobian-based VICBCT was greater or equal to that of the HU-based VICBCT . In addition, the ventilation accuracy of VICBCT increased at low gantry speeds. Thus, the image quality of VICBCT was affected by the change in gantry speed in both the imaging systems. Additionally, DIR regularization considerably influenced VICBCT in both the imaging systems. Our results have the potential to assist in designing CBCT protocols, incorporating VICBCT imaging into the functional avoidance planning process.